Iraq Social Accounting Matrix, 2011 - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
This data study includes Iraq Social Accounting Matrix (SAM) for the year 2011. The SAM includes 15 agricultural sectors (including livestock), 2 mining sectors (oil and rest), 3 industrial sectors, and 6 service sectors. This database draws information on income, expenditure and labor from Iraq Household Socio-Economic Survey (IHSES) and separates out households into 12 groups and production factors into 10 groups. The households are classified based on the gender of the household head , per capital expenditure quintiles of the households, and whether the household resides in rural or urban area. Similarly, production factors were dis-aggregated into 6 categories of labor ( 3 levels of skill and gender), 3 types of capital (agriculture, oil and rest) and land. This SAM gives the detailed representation of Iraqi economy and is an ideal database for conducting further analysis such as economy wide impact assessment, multiplier analysis, and trade flow.